Criminological Analysis of Motorcycle Theft - Agung Herwanto; Akmal Latif, Syahrul (Sisi Lain Realita, 2023)
In the current era of digitalization, there are many demands of life that must be met, starting from daily living needs and other living needs. Even today, to fulfill this, many of our people take negative actions so that these demands can be met. Like an act of theft. This theft is done secretly or secretly or not through legal means or theft is carried out secretly or without other people knowing what they are doing. This research is a qualitative type of research and in this research we will analyze the causes of the crime of motorbike theft as in Criminology which is a science that investigates the symptoms of crime or the causes and consequences of The crime itself was caused by the motorbike owner's negligence regarding his motorbike, making it easier for the perpetrator to launch the action. Not only that, but the factors that cause perpetrators to steal motorbikes are economic factors and other factors.